The impression of village fund management in traditional villages - Lakilaki, Eogenie; Soediro, Achmad (Jurnal Mantik, 2024)
This research aims to analyze the influence of accountability, transparency and community participation on the village funds management (ADD) to increase Good Village Governance (GVG) in Tenganan Pegringsingan Village, Bali Province. Data was collected by distributing questionnaires and analyzed using multiple linear regression. The results show that accountability, transparency and community participation have a positive and significant effect on ADD management, and these three variables simultaneously have a positive and significant effect on ADD management. The practical implication of the research results for Government officials and the Traditional Kelian of Tenganan Pegringsingan Village is the creation of ADD management that is in accordance with Minister of Home Affairs Regulation Number 77 of 2020 concerning Technical Guidelines for Regional Financial Management